Parent and physician decision making in children with suspected ear infection presenting to a children's hospital emergency department. - Page, Jacqueline. (University of Ottawa (Canada), 2000)
Problem statement. This study examines the parent decision to consult a physician, a physician diagnostic decision and a treatment decision in a common childhood illness, acute otitis media (AOM). Method. Physicians and parents of children with suspected ear infection consulting an emergency department in March--June 1998 were surveyed to describe factors related to parent and physician diagnostic and treatment decisions. Results. Parents consulted the ED when their usual caregiver was unavailable. Thirty-eight percent of 769 children were diagnosed with AOM. Presence of earache, absence of fever, parent suspicion of ear infection, and physician work status were each significantly associated with AOM diagnosis. Antibiotics were prescribed for 78% of AOM children. Presence of earache, fever and physician work status was each significantly associated with a decision to prescribe antibiotics. Conclusion. This study provides information to support the development of a physician-parent guide to the diagnosis and treatment of AOM.
Keywords: Health Sciences, Medicine and Surgery.